ANALISIS GOOD CORPORATE GOVERNANCE DI SEKTOR MANUFAKTUR: PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE, RETURN ON ASSET, DAN UKURAN PERUSAHAAN TERHADAP NILAI PASAR PERUSAHAAN - Zulfikar, Zulfikar (Universitas Muhammadiyah Surakarta, 2006)
This study aims to test empirically the impact of implementation good corporate governance on themarket value of firms. The Good Corporate Governance Perception Index (IICG) used in this studydeveloped by KNKCGI (2001). Moreover, this study also investigated whether investors also considerother Good Corporate Governance variables. This study examines twenty-eight companies that implemented Good Corporate Governance inJakarta Stocks Exchange during 2001 to 2002. Regression model analysis is used to identify the effectimplementation Good Corporate Governance on market value of firm. The result show that there areno positively impact to implementation Good Corporate Governance with market value of firms.